2017
DOI: 10.1007/s12272-017-0980-4
|View full text |Cite
|
Sign up to set email alerts
|

Valsartan regulates TGF-β/Smads and TGF-β/p38 pathways through lncRNA CHRF to improve doxorubicin-induced heart failure

Abstract: This study investigated the interaction among valsartan (VAL), TGF-β pathways, and long non-coding RNA (lncRNA) cardiac hypertrophy-related factor (CHRF) in doxorubicin (DOX)-induced heart failure (HF), and explored their roles in DOX-induced HF progression. HF mice models in vivo were constructed by DOX induction. The expression of CHRF and TGF-β1 in hearts was detected, along with cardiac function, caspase-3 activity, and cell apoptosis. Primary myocardial cells were pretreated with VAL, followed by DOX indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Bcl6 is emerging as a key oncoprotein and therapeutic target with a powerful transcriptional repression effect that silences hundreds of genes (Cardenas et al, ). Recently, Bcl6 was reported to suppress renal inflammation via negatively regulating NLRP3 transcription in a human renal tubular epithelial cell line (Chen et al, ). Bcl6 also attenuates allergic airway inflammation (Seto et al, ) and inflammation in the process of atherosclerosis (Barish et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl6 is emerging as a key oncoprotein and therapeutic target with a powerful transcriptional repression effect that silences hundreds of genes (Cardenas et al, ). Recently, Bcl6 was reported to suppress renal inflammation via negatively regulating NLRP3 transcription in a human renal tubular epithelial cell line (Chen et al, ). Bcl6 also attenuates allergic airway inflammation (Seto et al, ) and inflammation in the process of atherosclerosis (Barish et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Sakr et al ( 12 ) investigated the effect of Val on DOX-induced cardiotoxicity in rats, and found that concurrent or post-but not pre-treatment with Val attenuated DOX-induced cardiotoxicity by inhibiting oxidative stress, apoptosis and senescence. Another study reported that Val alleviated DOX-induced cardiac dysfunction via regulation of the TGF-β signaling pathway ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an incurable and progressive disease, heart failure (HF) has high morbidity and mortality rates in most countries including China [ 1 ]. According to previous studies, the prevalence of HF ranges from 1% to 2% and increases among people of age 65 years and older [ 2 ].…”
Section: Introductionmentioning
confidence: 99%